Ghost Towns of the American West - Silverberg, Robert (Book collections on Project MUSE., 1994)
With a historian's attention to fact and a novelist's gift for dramatic storytelling, celebrated science fiction author Robert Silverberg brings these adventures back to life in the rowdy splendor of their heyday in Ghost Towns of the American West.